2011
DOI: 10.4172/2155-9880.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Complete Atrioventricular Block During Cisplatin Infusion: A Case Report

Abstract: Cisplatin is one of the most effective chemotherapeutic agents used in the treatment of malignancies. The clinical use of cisplatin is limited by its severe adverse effects. Acute or long term cardiotoxicity is the most important doselimiting toxicity of cisplatin Cases of angina, myocardial infarction, and atrial arrhythmia have been reported during continuous infusion of cisplatin, but atrioventricular block (AV) has not been reported. Herein, we report a case with recurrent AV block that developed during ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Possible explanation for this cardiotoxic effect of cisplatin may be found in evidence for the deposition of cisplatin in the region of sinoatrial node [59] . It has been reported that cisplatin-induced bradicardia may be related to recurrent AV block [51] Also, negative chronotropic effect of cisplatin was observed after acute cisplatin application in isolated perfused rat heart [43] . However, NAC application in combination with cisplatin completely reversed cisplatin-induced negative chronotropic effect ( Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Possible explanation for this cardiotoxic effect of cisplatin may be found in evidence for the deposition of cisplatin in the region of sinoatrial node [59] . It has been reported that cisplatin-induced bradicardia may be related to recurrent AV block [51] Also, negative chronotropic effect of cisplatin was observed after acute cisplatin application in isolated perfused rat heart [43] . However, NAC application in combination with cisplatin completely reversed cisplatin-induced negative chronotropic effect ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Ischemia syndrome, palpitation and myocardial infarction can occur during treatment with cisplatin, or even as long-term consequences [57] . Treatment with cisplatin can be also associated with occasional complete atrioventricular block, hypotension [51] and recurrent sinus bradycardia [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cardiac toxicity resulting from cisplatin treatment has been described (Pai and Nahata, 2000). Cisplatin-induced cardiotoxic effects have been reported to manifest through changes in electrocardiography (Al-Majed et al, 2006; Raja et al, 2013) and arrhythmias, which include ventricular arrhythmias, supraventricular tachycardia, atrial fibrillation, occasional sinus bradycardia and occasional complete atrioventricular block (Yavas et al, 2008; Guglin et al, 2009; Ozcan et al, 2011). Myocarditis, pericarditis, and angina have also been reported in cisplatin-induced cardiac toxicity (Khan et al, 2012; Bano et al, 2013).…”
Section: Clinical Manifestations Of Cisplatin-induced Cardiac Toximentioning
confidence: 99%
“…CDDP-induced cardiotoxic effects have been observed through serious changes in electrocardiography and arrhythmias, which include ventricular arrhythmias, supraventricular tachycardia, atrial fibrillation, occasional sinus bradycardia, and occasional complete atrioventricular block ( 6 - 10 ). These cardiotoxic (and other potentially unknown) problems eventually lead to congestive heart failure and sudden cardiac death ( 11 ).…”
Section: Introductionmentioning
confidence: 99%